Roman Britain a sourcebook - Ireland, Stanley (Routledge sourcebooks for the ancient world, 2008)
This collection, based on the author's many years of teaching the subject to undergraduates, is a thorough and scholarly compilation of all the sources of evidence for the history of Britain under Roman rule.